Antibiofilm activity of carboxymethyl chitosan on the biofilms of non-Candida albicans Candida species. (20th September 2016) - Tan, Yulong; Leonhard, Matthias; Moser, Doris; Schneider-Stickler, Berit
Highlights: Carboxymethyl chitosan inhibited biofilm of non- albicans Candida species. Carboxymethyl chitosan inhibited the activity of planktonic cells grown and adhesion. Carboxymethyl chitosan blocked further development of biofilms at different stages. Abstract: Although most cases of candidiasis have been attributed to Candida albicans, non- C. albicans Candida species have been isolated in increasing numbers in patients. In this study, we determined the inhibition of carboxymethyl chitosan (CM-chitosan) on single and mixed species biofilm of non- albicans Candida species, including Candida tropicalis, Candida parapsilosis, Candida krusei and Candida glabrata . Biofilm by all tested species in microtiter plates were inhibited nearly 70%. CM-chitosan inhibited mixed species biofilm in microtiter plates and also on medical materials surfaces. To investigate the mechanism, the effect of CM-chitosan on cell viability and biofilm growth was employed. CM-chitosan inhibited Candida planktonic growth as well as adhesion. Further biofilm formation was inhibited with CM-chitosan added at 90 min, 12 h or 24 h after biofilm initiation. CM-chitosan was not only able to inhibit the metabolic activity of Candida cells, but was also active upon the establishment and the development of biofilms.